Unjuk Kerja Model Turbin Angin Poros Horizontal Dengan Variasi Bentuk Blade - sarjono sarjono (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2019)
The purpose of this research is to find out the Horizontal shaft wind turbine Model work with Blade shape variations. In this research the variation is done on the blade shape. The Blade is designed with curved shape, inverted linear taper and rectangular with size 8 cm x 20 cm at 20o tilt angle with wind speed 7; 8; 9; 10; and 11 m/s. The results showed that variations in the blade shape affected the horizontal shaft wind turbine work. Brake Horse Power (BHP) is maximally obtained with a rectangular shape blade of 1, 1 watt at a wind speed of 11 m/s with a torque of 0.0221 Nm on the blade shape and the same wind speed. While the high efficiency is achieved with a rectangular shape blade at a wind speed of 7 m/s by 21%.